Assessment of an Online Training Tool for the Automated Unit-Dose Dispensing System (ADS) Process - Hamon Marie; Capelle Flora; Passemard Raphaël; Gourieux Bénédicte (De Gruyter, 2019)
Automated unit-dose dispensing system (ADS) of oral solid medication is a complex and sensitive production process in the drug distribution system. Hence, an appropriate training of hospital pharmacy technicians (HPT) is essential. A basic training (observational and practical) of 3 weeks is first organized to evaluate the HPT, followed by an interview with both the pharmacist and the HPT chief. The importance of the human factor (daily routine and repetitive tasks) showed by the risks analysis within this process has led us to search new learning methods to keep the team engaged. An e-learning training was selected in order to further complete the HPT initial training but also as a continuous training to the HPTs who are already working in the ADS process.